2015
DOI: 10.1080/01425692.2015.1093409
|View full text |Cite
|
Sign up to set email alerts
|

Student-centered instruction and academic achievement: linking mechanisms of educational inequality to schools’ instructional strategy

Abstract: Research in the sociology of education argues that the educational system provides different learning opportunities for students with different socioeconomic backgrounds and that this circumstance makes the educational process an important institutional context for the reproduction of educational inequality. Using combined survey and register data of more than 56,000 students in 825 schools, this paper conducts the first empirical test of the argument that instructional strategies that emphasize student respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 41 publications
0
30
1
8
Order By: Relevance
“…The constraining effect of red tape is central in the red tape literature on performance, where it can constrain managers in relation to promoting employee motivation because of human resources red tape or redistributing resources because of financial red tape (Pandey, Coursey, and Moynihan ; Pandey and Moynihan ). Similarly, perceived red tape can constrain frontline staff behavior, as in relation to the choice and adjustment of teaching methods within education, which are important factors in student learning (Andersen and Andersen ; Hattie ).…”
Section: Why Should Red Tape Perceptions Matter For Performance?mentioning
confidence: 99%
“…The constraining effect of red tape is central in the red tape literature on performance, where it can constrain managers in relation to promoting employee motivation because of human resources red tape or redistributing resources because of financial red tape (Pandey, Coursey, and Moynihan ; Pandey and Moynihan ). Similarly, perceived red tape can constrain frontline staff behavior, as in relation to the choice and adjustment of teaching methods within education, which are important factors in student learning (Andersen and Andersen ; Hattie ).…”
Section: Why Should Red Tape Perceptions Matter For Performance?mentioning
confidence: 99%
“…However, lacking such dispositions, students from low SES backgrounds may fail to profit from student-centered instruction. In support of this hypothesis, Andersen and Andersen (2017) found that student-centered instruction is negatively associated with mathematics achievement among low SES Norwegian high school students, but not among their higher SES peers.…”
Section: Teaching and Educational Equitymentioning
confidence: 89%
“…With regards to instruction, some authors suggest that student-centered instruction may benefit students from affluent families, but detrimental for lower SES students (Andersen & Andersen, 2017). This argument is based upon sociological theories regarding the incompatibility between the school's linguistic/cultural codes with the linguistic/cultural codes of lower SES families (Sadovnik, 1991).…”
Section: Teaching and Educational Equitymentioning
confidence: 99%
“…Discussions, presentations, elaborations, and critique activities that formed key aspects of constructivist instruction enhanced understanding and memory of participants in the constructivist group (Andersen & Andersen, 2017;Connell et al, 2016;Hsu et al, 2019;Izzo, 2012;Kharb et al, 2013;Laal et al, 2013;McKnight et al, 2016;Montrieux et al, 2015;Öhrstedt & Lindfors, 2018;Zenda, 2017). The engagement phase provided learners with opportunity and much needed scaffolding which made them more focused and clearer on how to carry out investigations and what to discuss in the groups.…”
Section: Comparing Constructivist and Conventional Instructionmentioning
confidence: 99%